2008
DOI: 10.1007/s11192-007-1888-4
|View full text |Cite
|
Sign up to set email alerts
|

Population modeling of the emergence and development of scientific fields

Abstract: We analyze the temporal evolution of emerging fields within several scientific disciplines in terms of numbers of authors and publications. From bibliographic searches we construct databases of authors, papers, and their dates of publication. We show that the temporal development of each field, while different in detail, is well described by population contagion models, suitably adapted from epidemiology to reflect the dynamics of scientific interaction. Dynamical parameters are estimated and discussed to refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
97
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 22 publications
2
97
0
4
Order By: Relevance
“…The fields vary greatly in size and composition: from relatively modest-sized communities in theoretical physics such as cosmic strings or cosmological inflation, in which authors have similar training; to benchtop biomedical topics like research on scrapie and prions, which incorporate co-authors of varied expertise who work together on a narrowly-defined problem; to huge interdisciplinary fields like nanotechnology and sustainability science, which feature authors from a wide range of specialties. Whereas we have examined other aspects of the growth of several of these fields in previous work [7,17], the two largest fields in our sample -sustainability science and nanotechnology -represent brand-new datasets. Table 1.…”
Section: Characterizing Growth Over Timementioning
confidence: 99%
See 3 more Smart Citations
“…The fields vary greatly in size and composition: from relatively modest-sized communities in theoretical physics such as cosmic strings or cosmological inflation, in which authors have similar training; to benchtop biomedical topics like research on scrapie and prions, which incorporate co-authors of varied expertise who work together on a narrowly-defined problem; to huge interdisciplinary fields like nanotechnology and sustainability science, which feature authors from a wide range of specialties. Whereas we have examined other aspects of the growth of several of these fields in previous work [7,17], the two largest fields in our sample -sustainability science and nanotechnology -represent brand-new datasets. Table 1.…”
Section: Characterizing Growth Over Timementioning
confidence: 99%
“…First, as our "mean-field" population-modeling has shown, the total number of authors (nodes), N (t), plays the role of the relevant time-like dynamical variable [7]. For example, we found that the total number of articles grows as a simple power-law of the total number of authors, even as both quantities display more complicated growth patterns when measured with respect to time, t. Thus we may adopt N (t), the number of authors in a given field at time t, as our basic time-like variable, akin to the kinds of rescaling commonly adopted in cosmological models such as the universal scale factor, a(t),…”
Section: Characterizing Growth Over Timementioning
confidence: 99%
See 2 more Smart Citations
“…Luís M. A. Bettencourt et al (2008) analyze the temporal evolution of emerging areas within several scientific disciplines according to numbers of authors and publications using contagion models developed in epidemiology.…”
mentioning
confidence: 99%